Benefits of the Pilates method for postmenopausal women: systematic review (Research, Society and Development, 2020)
Introduction: the climacteric is a period in the woman's life cycle represented by the passage between the reproductive and non-reproductive period, in which menopause occurs. In this phase, several physiological changes occur, such as vasomotor and psychological symptoms, sleep disorders, osteoporosis and loss of muscle mass. Objective: to identify the main benefits that the practice of the Pilates method offers for postmenopausal women. Materials and methods: systematic review performed on LILACS, MedLine, PubMed and SciELO databases, using the descriptors "Pilates method" and "menopause". Studies published since 2010, in Portuguese, English and Spanish, which used Pilates training with post-menopausal women were included. The methodological quality of the articles found was assessed using the PEDro scale. Results: only three controlled and randomized clinical trials were selected, with a sample varying between 41 and 110 participants and mean age between 59 and 69 years. In all studies, the time for each session was 60 minutes and the frequency was twice a week. Two studies used a 12-week protocol and one adopted a 30-week exercise program. All were considered of good methodological quality by the PEDro scale. Conclusion: the main results found show that the practice of the Pilates method can influence the balance, posture, sleep, anxiety and depression, fatigue and respiratory function of postmenopausal women.